2016
DOI: 10.1038/srep30318
|View full text |Cite
|
Sign up to set email alerts
|

The 7 × 1 Fermi Surface Reconstruction in a Two-dimensional f -electron Charge Density Wave System: PrTe3

Abstract: The electronic structure of a charge density wave (CDW) system PrTe3 and its modulated structure in the CDW phase have been investigated by employing ARPES, XAS, Pr 4 f RPES, and first-principles band structure calculation. Pr ions are found to be nearly trivalent, supporting the CDW instability in the metallic Te sheets through partial filling. Finite Pr 4 f spectral weight is observed near the Fermi level, suggesting the non-negligible Pr 4 f contribution to the CDW formation through the Pr 4 f -Te 5p hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…We note that the in-gap photoemission intensity observed here is consistent with previous ARPES studies of RTe 3 [2,4,15,18,21]. However, the phenomenon was not discussed.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We note that the in-gap photoemission intensity observed here is consistent with previous ARPES studies of RTe 3 [2,4,15,18,21]. However, the phenomenon was not discussed.…”
supporting
confidence: 92%
“…Moreover, recent studies of de Haas van Alphen and Shubnikov-de Haas QOs in high mobility crystals have revealed high-frequency QOs that should originate from large FS elements, covering a substantial fraction of the Brillouin zone (BZ) [7,13]. However, there are no obvious candidates for such large FS elements in the CDW phase, since the CDW is expected to lead to a large gap in most of the BZ, as has been confirmed by angle-resolved photoemission spectroscopy (ARPES) in numerous studies [2,3,[13][14][15][16][17][18][19][20][21]. The assignment of most of the observed QOs to FS elements is still an outstanding problem.…”
mentioning
confidence: 96%
“…4 b, c). This gap has been referred to as the CDW gap in LaTe 3 36 and other RTe 3 systems 45 , 49 , 50 , 62 , 64 . A discussion about the variation of the CDW gap of LaTe 3 with k x and k y is provided in the Supplementary Note 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Rare earth tellurides (ReTe x ) exhibit a diverse range of intriguing properties including charge density waves (CDW) [1][2][3][4], two-dimensional (2D) magnetism [5,6], as well as thermal hysteresis effects on resistivity and CDW gap [7,8], making them promising candidates for studying electron correlation phenomena and various applications in spintronics. Among these materials, europium tellurides are particularly unique due to the half-filled 4f orbital of the Eu atom ([Xe] 4f 7 6s 2 ).…”
Section: Introductionmentioning
confidence: 99%